2016
DOI: 10.12944/crnfsj.4.2.07
|View full text |Cite
|
Sign up to set email alerts
|

Feed Efficiency and Serobiochemical Profile of Wistar Rats Fed With Spirulina As Functional Food

Abstract: Spirulina is an algae that grow in fresh and sea water and itself known to the human community with its unique Neutraceuticals properties, generally produced from the species named Arthrospira platensis, and Arthrospira maxima. Arthrospira species were cultivated throughout the world to fulfil the need of human dietary supplementation. An experimental study was planned to know the effect of spirulina supplementation on serum biochemical profile of Wistar albino rats as model study. Test results clearly denoted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…The feed given to each group was weighed and recorded on daily basis. Split and leftover feed were also measured in order to get the exact estimation of daily feed intake and feed conversion ratio 16 . …”
Section: Methodsmentioning
confidence: 99%
“…The feed given to each group was weighed and recorded on daily basis. Split and leftover feed were also measured in order to get the exact estimation of daily feed intake and feed conversion ratio 16 . …”
Section: Methodsmentioning
confidence: 99%
“…Total weight gain and average dry matter intake of animals were similar in all the dietary treatments and presented in Table 3. James et al (2002) and Manjula et al (2016) observed similar total dry matter intake in rats.…”
Section: Resultsmentioning
confidence: 78%
“…Estimation of body weight (BW) and feed intake (FI) as biological parameters was as follow: Rats weight was measured and recorded weekly then increasing in body weight (BW) of rats in all groups at the end of the experiment represented as a line curve. Daily feed intake (FI) in gram evaluated by the difference between food offered ad libitum-and feed refusals [24].…”
Section: Estimation Of Biological Parametersmentioning
confidence: 99%